Perspektif Hukum Islam Terhadap Permainan Anak (Lotre) - Nur Zhafira, Nasywa; Asri Syam, Tazkiya; Nurul Latifah, Siti; Khairani Rangkuti, Sonia Winda; Br. Regar, Lailatul Husna (Tabayyun : Journal Of Islamic Studies, 2024)
Games or toys are a form of entertainment or fun. As time goes by, games become more diverse. Apart from being used for fun or entertainment, games can also train children's growth. Children's toys are products made or designed for children under 14 years of age. Games by type, children's toys can be divided into two, namely toys and games. Toys are a type of children's toy whose function is as entertainment for children. This is different from games where in every game there are winners and losers, such as monopoly, snakes and ladders, lottery and so on. Lottery itself is a custom that existed Long before the arrival of Islam, lottery during the Jahiliyah era was used to determine whether a person was good or bad and was played in front of idols. However, nowadays, the world of children's games such as lottery often involves pictures. Lottery games for children use a luck system, so that in each game there will be lucky and unlucky ones. Lucky buyers will get prizes, while unlucky buyers get nothing. Buying and selling lottery children's toys is prohibited according to Islamic law because the objects being traded are haram goods. Apart from that, there is also the practice of drawing lots which will harm one of the parties. Buying and selling lottery children's toys is also contrary to Law Number 7 of 1974 concerning Controlling Gambling because this practice is contrary to norms, morals, decency and the law, and is dangerous to the lives of society, the nation and the State.